Examining Translation Techniques in the Health Article on Benefits of Getting the COVID-19 Vaccine - ORVIN GRENDI PUTRI KEMANGI (IJOTL-TL (Indonesian Journal of Language Teaching and Linguistics))
The types of translation techniques proposed by prominent figures support the translators to ease the process of converting source text (ST) into target text (TT). Regarding the translation process and product, this study applied Vinay and Darbelnetâ€™s techniques (1958) to examine the translation of a medical text published on July 13 2022 in University of Missouri website. The text discusses the benefits of getting COVID-19 vaccine. The goal of choosing this article is to provide more information about the advantages of COVID-19 vaccine in Indonesian. Thus, the ST that is used in this study is English and the TT in Indonesian. This translation study used descriptive qualitative research that tends on the medical text in form of article as the data of the study.  In this study, the translation process of the text involves 7 techniques of Vinay and Darbelnet including literal translation, omission, borrowing, transposition, paraphrase, explication, and modulation. The most used technique in translating the text is literal translation that focuses on the structure or forms of the text and the least used techniques are modulation and explication.